Beyond the prison gates : punishment and welfare in Germany, 1850-1933 - Rosenblum, Warren (Studies in legal history., 2008)
"Germany today has one of the lowest incarceration rates in the industrialized world, and social welfare principles play an essential role at all levels of the German criminal justice system. Warren Rosenblum examines the roots of this social approach to criminal policy in the reform movements of the Wilhelmine and Weimar periods, when reformers strove to replace state institutions of control and incarceration with private institutions of protective supervision."